Aging in an Era of Fake News. (June 2020) - Brashier, Nadia M.; Schacter, Daniel L.
Misinformation causes serious harm, from sowing doubt in modern medicine to inciting violence. Older adults are especially susceptible—they shared the most fake news during the 2016 U.S. election. The most intuitive explanation for this pattern lays the blame on cognitive deficits. Although older adults forget where they learned information, fluency remains intact, and knowledge accumulated across decades helps them evaluate claims. Thus, cognitive declines cannot fully explain older adults' engagement with fake news. Late adulthood also involves social changes, including greater trust, difficulty detecting lies, and less emphasis on accuracy when communicating. In addition, older adults are relative newcomers to social media and may struggle to spot sponsored content or manipulated images. In a post-truth world, interventions should account for older adults' shifting social goals and gaps in their digital literacy.